EXPERIENCE OF FOREIGN COUNTRIES IN COMBATING ILLEGAL TURNOVER OF NARCOTIC DRUGS AND PSYCHOTROPIC SUBSTANCES - Musaev Djamaliddin Kamalovich (Galaxy International Interdisciplinary Research Journal, 2023)
The article is devoted to a comparative analysis of systems for combating offenses in the field of trafficking in narcotic drugs and psychotropic substances at the international level. This article discusses the problems of detecting and preventing offenses, as well as control over the circulation of narcotic drugs and psychotropic substances in various countries of the world. Analyzed the characteristic features of the approach to overcoming the current situation in the field of drug use, the use of various methods of counteracting this negative phenomenon in the process of suppressing illegal actions. Revealed and substantiated the need for joint use of methods to combat the global problem of all mankind. On the basis of the study, the author proposes to pay attention to the world experience in the prevention of offenses. The purpose of this work is to analyze the advantages and disadvantages of individual legal institutions of foreign criminal law and predict the consequences of their application in the Republic of Uzbekistan.